Enriching Students’ Vocabulary by Using Frontloading Strategy - Nadia Pratiwi Kasim; Rasuna Rasid Talib; Sri Agriyanti Mestari (Research Review: Jurnal Ilmiah Multidisiplin, 2023)
The aim of this research is to find out whether frontloading strategy can enrich significantly the students’ vocabulary of SMK Negeri Model Gorontalo or not. This research applied the pre-experimental research design, with one Pre-test and Post-test design which consisted of seven meetings include the treatments. The population in this research was tenth grade students of SMK Negeri Model Gorontalo which consisted of 105 students. The sample was taking by purposive sampling technique and the total number of samples was 35 students in class Ⅹ TKJ. The result of the data analysis show that there is an improvement between the result of pre-test and post-test. The mean score of the pre-test of the students was 50,02 and the post-test was 75. It also shown that the t-test value (8,50) was higher than the t-table value (2,032). It means that the Alternative Hypothesis (H1) was accepted, and the Null Hypothesis (H0) was rejected. Thus, the using Frontloading Strategy can enrich significantly the students’ vocabulary at tenth grade students of SMK Negeri Model Gorontalo.